Effect of pulse duration and current on machining performance during electrical discharge machining (EDM) of allegheny ludlum D2 tools steel (UNS T30402) - Shahruzaman Bin Sulaiman (Kulliyyah of Engineering, International Islamic Universiy Malaysia, 2013)
Electrical discharge machining (EDM) is a process for shaping hard metals and forming deep complex-shaped holes by arc erosion in all kinds of electrical conductive materials. In the present day, there is a huge demand for the advanced materials with high strength, high hardness and temperature resistance in automobile, aeronautics, nuclear, mould and dies making industries. The purpose of this research is to study the effect of pulse duration and current on performance of EDM process of Allegheny Ludlum D2 Tool Steel (UNS T30402). The effect of varying the machining parameters on the machining responses such as material removal rate (MRR), electrode wear rate (EWR), wear ratio (WR) and surface roughness (Ra) have been investigated. In addition, this research also emphasizes on the study related to the effect of shape configuration of electrodes on the performance of EDM. The electrodes were made with circular and triangular shape with constant cross-sectional area of 100mm². It was found that the pulse duration and current give significant effect on MRR, EWR, WR and Ra. An increase in the pulse durations causes an increase in the MRR and Ra, but a decrease in the EWR and WR. Meanwhile, the effect of currents on EDM performance shows that the increasing currents led to an increase in the MRR, EWR, WR and Ra. Finally, from all the results obtained, several analyses have been made to compare the machining performance results between circular shaped electrode and the triangular shaped electrode. It was found that the value of MRR for circular shaped electrode was higher than that of triangular shape electrode. Meanwhile, the higher value for EWR, WR and Ra was found at the triangular shaped electrode.